PENGARUH TOTAL ASSET TURNOVER (TATO) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI INTERVENING VARIABLE (SURVEY PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 - Sarif Hidayat (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
This study aims to determine the effect of Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) on Share Prices with Profitability as Intervening Variables in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX). Where Profitability used in the study is Return on Assets (ROA). This study uses secondary data, which is in the form of financial reports obtained from the Indonesia Stock Exchange (IDX) website. The samples used were 6 companies from 17 populations in 2012-2017 in the selection of samples conducted by purposive sampling. The statistical method used is panel data path analysis. The results showed that Total Asset Turnover (TATO) directly had a significant negative effect on Stock Prices. Likewise, the Debt To Equity Ratio (DER) directly has a significant positive effect on stock prices. While indirectly the Total Asset Turnover (TATO) mediated by Profitability affects the Stock Price. Meanwhile, indirectly the Debt To Equity Ratio (DER) mediated by Profitability has no effect on the Share Price.